Pomen (moč) ljubezni pri vodenju in pri zavzetosti zaposlenih v javni upravi - Pličanič, Senko (Javna uprava, 2017)
The author discusses importance of love (self-love) in our life. Love and happiness could only be achieved through the balance between spiritual and material dimensions of our life. The spiritual dimension has been removed from our lives in the last centuries. The author, therefore, suggests to modify the sustainable development principle to incorporate spiritual development as well as in order to establish a comprehensive sustainable development principle - as an exit plan for the humanity. Due to the importance of public sector and public administration it is very important to incorporate spiritual development into all-life training of public sector employees. Due to the importance of leadership, spiritual development and self-love as a result should be considered as one of the key qualifications for leaders in politics and public administration.
Keywords: hapiness; javni sektor; leadership; ljubezen; love; politics; politika; public sector; sreča; sustainable development; trajnostni razvoj; vodenje